The characteristics of civil organisations for sports with special regards to employment - Dajnoki, Krisztina; Fenyves, Veronika; Bácsné Bába, Éva; Kőmíves , Péter Miklós; Szabados, György Norbert (International Journal of Engineering and Management Sciences, 2020)
The aim of our article to compare the characteristics of the civil organisations operating in Hugary and in Romaina with special regards to the employment characteristics of the sport civil associations. We ascertained during our research work that the civil sector of the two investigated countries show several similarities. One of these similarities is the lag from the same sectors operating is Western-European countries. The use of volunteer working is a main characteristic of the employment in the civil sector however the paid work plays an important role too.